NATURAL POLYACETYLENE COMPOUNDS - D. A. Konovalov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Polyacetylenes (polyynes) are compounds which contain two or more triple bonds in its structure. About 2 000 different polyacetylenes and biogenetically related substances were identified in 24 families of higher plants. However, most of these compounds were found in seven families of flowering plants: Apiaceae (Umbelliferae), Araliaceae, Asteraceae (Compositae), Campanulaceae, Olacaceae, Pittosporaceae and Santalaceae. Polyacetylenes are relatively unstable, chemically and biologically active compounds, and present in fungi, microorganisms, marine invertebrates and other organisms except for plants. Acetylenes form distinct specialized group of chemically active natural compounds, which are biosynthesized in plants of unsaturated fatty acids. In addition to widespread aliphatic polyacetylenes thiophenes dithiacyclohexadienes (thiarubrines), thioethers, sulphoxides, sulphones, alkamides, chlorohydrins, lactones, spiroacetal enol ethers, furans, pyrans, tetrahydropyrans, isocoumarins, aromatic acetylenes were also found in plant species. Polyacetylenes are localized in different plant organs, and can be found both individually and as a compound with carbohydrates, terpene, phenolic and other compounds. Many polyacetylenes are found in the composition of the essential oils of plants and it confirms their strongly marked ecological functions. From biological point of view these compounds are often synthesized by plants as toxic or bitter antifeedants, allelopathic compounds, phytoalexins or broadly antibiotic components. Polyynes are strong photosensitizers. They exhibit anti-inflammatory, anti-coagulant, anti-bacterial, antituberculosis, anti-fungal, anti-viral, neuroprotective and neurotoxic activity. Immunostimulatory influence associated with certain allergenicity of some of these substances was established. Therefore, without a doubt polyacetylenes are of interest for the modern pharmacy and medicine.